Stories, Myths and Rituals: Life in the Mentawai Archipelago in a Globalism Analysis - Delfi, Maskota; Weintré, Johan; Arifin, Zainal; Pujiraharjo, Sidarta; Oktayanti, Yetty; Irwandi, Ade (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
Myths, rituals and life stories are interconnected and conveyed through long-standing oral traditions, making them important cultural assets of indigenous peoples around the world. In the Mentawai Islands, myths and rituals are inseparable from the daily lives of the people. The myths are not only communicated within the community but also revealed to outsiders. This research deviates from earlier literature as it aims to explore the relationship between traditional rituals, life stories, myths and modern dynamics in the different valleys to trace the ancestral claims of land ownership. The study employed a qualitative approach. Data was collected through observation and in-depth interviews with Sikerei (shaman), clan elders and notable clan individuals in the thinly populated watersheds in south Siberut Island, complemented by a literature review. The findings show that various rituals and myths about the life journey of the Mentawai people are important to current values. Extended with a unique culture of body tattoos, botanical knowledge, sago staple food consumption combined with animal protein feasts. It can be concluded that myths have a relationship with their living practices they lived, the formation and strengthening of their cultural identities, belief systems and clan land claims in Mentawai. It suggests their indigenous knowledge can opens up a power to see what is not evident to the average mind and contributes to different shades of feeling and experiences.